INVESTIGATION OF ADHESION CAPABILITY OF LUBRICANTS ON THE BASIS OF ORGANICSILICON POLYMERS FOR CASTING OF ALUMINIUM ALLOYS UNDER THE PRESSURE - A. M. Mihaltsov; A. A. Pivovarchik (Литьë и металлургия, 2007)
It is shown that for getting of uniform coating, possessing good adhesion to the accessory surface, the lubricants containing silicon-organic compounds should be used.